2019
DOI: 10.1177/1557085119877248
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in Youth Exposure to Community Violence: A Partial Test of Power-Control Theory

Abstract: Youths’ exposure to community violence increases their risk for harmful emotional and behavioral outcomes. Several family management strategies protect youth against exposure though there is scant literature exploring whether their application is gendered. Using data from the Project on Human Development in Chicago Neighborhoods, we draw from power-control theory to assess gender differences in family management strategies and the extent to which this accounts for boys’ greater exposure to neighborhood violenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 66 publications
0
5
0
Order By: Relevance
“…A study of Black adolescent males in an under‐resourced neighborhood found that their perception of parental expectations related to violence (e.g., “Do your parents want you to stay away from situations where you could get into a fight?”) significantly predicted their self‐efficacy in avoiding violence (Thomas et al, 2016). Related, parents may endorse gendered attitudes about violence that can impact parenting behaviors related to restrictiveness and unstructured socializing and subsequent exposure to violence (Antunes et al, 2020). Future studies should consider parental attitudes and messaging surrounding parenting behaviors and child coping strategies in response to violence exposure.…”
Section: Discussionmentioning
confidence: 99%
“…A study of Black adolescent males in an under‐resourced neighborhood found that their perception of parental expectations related to violence (e.g., “Do your parents want you to stay away from situations where you could get into a fight?”) significantly predicted their self‐efficacy in avoiding violence (Thomas et al, 2016). Related, parents may endorse gendered attitudes about violence that can impact parenting behaviors related to restrictiveness and unstructured socializing and subsequent exposure to violence (Antunes et al, 2020). Future studies should consider parental attitudes and messaging surrounding parenting behaviors and child coping strategies in response to violence exposure.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings align with global reports that men are most likely to be both victims and perpetrators of violence, including weapon-related violence (United Nations Office on Drugs and Crime, 2019). Findings also indicate that although women might experience more violence in-home than in-community due to socialization and restrictions (Antunes et al, 2020), during adolescence they may not yet be at greater risk for in-home violence as compared to men. Nonetheless, our findings also show that the victimization gap between this sample of young men and women is the narrowest for in-home physical assaults, indicating that this may be the type and context of victimization for which women may be most at risk.…”
Section: Discussionmentioning
confidence: 94%
“…Therefore, the potentially moderating role of sex is an important factor in the examination of the effects of exposure to weapon-related violence. Studies also show that males report greater community violence victimization than women, whereas women might be at greater risk of victimization at home (Antunes et al, 2020; Springer & Padgett, 2000). This difference in the context of exposure suggests that while home and community victimization might be additive, men and women might have differential experiences that further complicate statistical models.…”
Section: Moderators That Might Vary Based On Types Of Assaultsmentioning
confidence: 99%
“…Boys are more likely than girls to experience community violence (e.g., Zona & Milan, 2011). In partial support of the power-control theory (e.g., Hagan et al, 1987) that links variations in common criminal activities between males and females to differential patterns of family management strategies and control processes, Lobo Antunes et al (2020) found that parents' greater protections outside the home over their adolescent daughters compared with their adolescent sons may account for girls' lesser exposure to neighborhood violence. In addition, 5-8-year-old girls were found to be less motorically active than boys even after maturation was taken into account (Eaton & Yu, 1989); girls outperformed boys in inhibitory control from toddlerhood to early school age (Kochanska et al, 1997).…”
Section: Sex Differencesmentioning
confidence: 99%